Development and performance evaluation of a hybrid-wire arc additive manufacturing system based on robot manipulators. (2022) - Lim, Wei Sheng; Dharmawan, Audelia Gumarus; Soh, Gim Song
Abstract: A Hybrid-Wire Arc Additive manufacturing system based on robotic manipulators was developed at the Singapore University of Technology and Design. The manufacturing approach employs a subtractive process that uses face milling after an additive process to prepare the surface for the next layer deposition. Test blocks were printed with and without the use of the hybrid process to understand their mechanical performance. The results show an improved flatness and an increase in ultimate tensile strength by more than 20% in three tested directions: vertical, lateral, and transverse directions at the cost of reduced ductility when a hybrid process is employed.